Crocetin Suppresses Uterine Ischemia/Reperfusion-induced Inflammation and Apoptosis through the Nrf-2/HO-1 Pathway - Peng, Shu; Wu, Yong; Wang, Ying (Current Molecular Medicine, 2023)
Background: Uterine ischemia/reperfusion (I/R) injury often occurs during many complex surgical procedures, such as uterus transplantation, cesarean, and myomectomy, which may lead to the loss of uterine function and failure of the operation. Crocetin (CRO), as one of the major active constituents from saffron extract, shows protective effects against reactive oxygen species, inflammation, and apoptosis. However, the role of CRO in protecting the uterus against I/R-induced injury has never been investigated. This study aims to clarify the protective role of CRO against I/R injury and the underlying mechanisms. Materials and Methods: Sprague-Dawley rats were randomly divided into five groups: the control group, I/R group, 20 mg/kg CRO-treated I/R group, 40 mg/kg CRO-treated I/R group, and 80 mg/kg CRO-treated I/R group. Rats were given daily gavages with different doses of CRO or vehicle for five consecutive days. The rat uterine I/R model was created by routine method with 1h ischemia and 3h reperfusion. The serum and uterine tissues were collected, the changes in malondialdehyde (MDA) level and superoxide dismutase (SOD) activity, the mRNA and protein levels of interleukin (IL)-1β, IL-6, tumor necrosis factor (TNF)-α and IL-10, the protein levels of B-cell chronic lymphocytic leukemia/lymphoma (Bcl)-2, Bcl-2-associated X protein (Bax), caspase-3, nuclear factor erythroid 2-related factor (Nrf)-2, and heme oxygenase (HO)-1, were measured. The histological changes were examined by HE staining. The number of apoptotic cells was analyzed by flow cytometry. Results: Uterine I/R significantly induced MDA level, suppressed SOD activity, upregulated levels of pro-inflammatory cytokines, down-regulated level of the antiinflammatory cytokine, induced caspase-3-dependent apoptosis, activated the protein expression of Nrf-2 and HO-1, and caused uterine damage. However, pre-administration of CRO effectively reversed I/R-induced above changes and further enhanced Nrf-2/HO- 1 activation in a dose-dependent manner. Conclusion: Pre-administration of CRO effectively alleviates I/R-induced oxidative stress, inflammation, apoptosis, and tissue injury probably through activating the Nrf- 2/HO-1 pathway, suggesting a protective role of CRO in I/R-induced uterus injury.
Keywords: uterus